Numerical Investigation of Gas‐Liquid Reacting Flow in a Jet‐Type Singlet Oxygen Generator. Issue 9 (1st July 2020) - Xu, Chao; Chen, Xi; Liu, Tingting; Huai, Ying; Chen, Guangwen
Abstract: A numerical simulation was carried out to investigate the process of gas‐liquid reaction in a jet‐type singlet oxygen generator by using volume‐of‐fluid coupled with large eddy simulation. The coupled hydrodynamic and reaction simulations provide detailed information about the reacting flow. Results reveal that the reaction aggravates the jet instability and affects the jet structure significantly due to the differential pressure around the liquid jet. The effects of gas velocity on chlorine conversion and the yield of singlet oxygen were investigated. The key is the increasing of the interface area rather than the convection. This numerical simulation study is convenient for the design of singlet oxygen reactors and the research of gas‐liquid two‐phase flow with reaction. Abstract : The gas‐liquid multiphase reacting flow in a jet‐type singlet oxygen generator was investigated by means of the volume‐of‐fluid method combined with large eddy simulation. By coupling hydrodynamic and reaction simulations, it could be stated that the reaction affects the jet structure significantly. The key factor is the enlargement of the interface area rather than the convection.